Textual phenomena addressing youth: Orthographic, typographic, and ideological aspects of the Greek-Cypriot dialect - Papadima, Aspasia (My University, 2025)
Two linguistic varieties dominate in Cyprus—Cypriot-Greek, which is the mother tongue of Greek-Cypriots, and Standard Modern Greek, which is the official language of the state. This chapter investigates Cypriot-Greek ‘Textese’, a localized variation of an informal and concise linguistic code that is a hybrid of writing and speech. The study adopts an ethnographic methodology to understand the written modes of communication and prevalent textual phenomena used by young Greek-Cypriots in contemporary media and on social networks. These phenomena include transliterations into different scripts, trans-scriptings and creative respellings, accent simulations, ‘deviant orthography’, manifestations of ‘digital orality’, and code-switching. Cypriot-Greek Textese is discussed in terms of ideology and semiotics, education and cultural identity, globalization, and glocality. Based on the research findings and utilizing sociolinguistic and typographic theories and sociosemiotic analysis, this chapter documents and analyzes the orthographic, typographic, and ideological aspects of Cypriot-Greek, which are shaped by the contemporary, multicultural, and European context of Greek-Cypriot youth.
Routledge Handbooks of Language Learning in the Global Context
Keywords: Cypriot-Greek Textese; Glocal textisms; Cyprenglish; Language ideology; Transliteration